Enforced Disappearances and Sri Lankan Human Rights Profile: An Analytical Reflection on Three Selected Enforced Disappearances Incidents in The Post-war Period - Amarasinghe, Kusal (Centre for the Study of Human Rights, University of Colombo, 2020)
According to the definition given by the United Nations’ Working Group on Enforced or Involuntary Disappearances which has appointed under the provisions of the International Convention for the Protection of all Persons from Enforced Disappearances, an enforced disappearance can be defined by three cumulative elements: (1) Deprivation of liberty against the will of the person; (2) Involvement of government officials, at least by acquiescence; & (3) Refusal to acknowledge the deprivation of liberty or concealment of the fate or whereabouts of the disappeared person. As a result of the dark era in the past three decades in Sri Lanka, thousands of enforced disappearances cases have reported. Among those cases, this article focuses on three selected enforced disappearance incidents which had happened during the final phase of the civil war period and the post-war period of Sri Lanka. It also discusses on the Political Approach of the Discourse on the Right not to Forcible Disappearance in Sri Lanka and the contemporary domestic legal framework against the enforced disappearance. The central question sought to be raised in this article is whether Sri Lanka has been able to guarantee the basic human rights of its citizens and how the political factor can be affected on it? However, this article has prominently tried to focus on the legal regime of the study area.
Keywords: Human Rights; Enforced Disappearances